Internship: Learning to be a doctor - Dhungana, V; Sthapit, B (Kathmandu University Medical Journal, 2010)
DOI: 10.3126/kumj.v7i4.2751 Kathmandu University Medical Journal (2009) Vol.7, No.4 Issue 28, 341-343